2014
DOI: 10.1017/s1368980014000317
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Arabic version of the Household Food Insecurity Access Scale in rural Lebanon

Abstract: Objective: To assess the validity and reliability of the Arabic version of the Household Food Insecurity Access Scale (HFIAS) in rural Lebanon. Design: A cross-sectional study on a sample of households with at least one child aged 0-2 years. In a one-to-one interview, participants completed an adapted Arabic version of the HFIAS. In order to evaluate the validity of the HFIAS, basic sociodemographic information, anthropometric measurements of the mother and child, and dietary intake data of the child were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 22 publications
7
34
1
3
Order By: Relevance
“…Findings from the present study show that almost 50% of interviewed households reported food insecurity with 42% suffering from moderate to severe food insecurity and 8% living with mild food insecurity. The prevalence of moderate to severe food insecurity among Beirut residents was found to be higher than that reported earlier by rural households in the Bekaa region and another semi-urban Southern Lebanese population (34% and 42%, respectively) [11, 12]. However, comparable food insecurity levels to those reported in Greater Beirut area were observed among urban communities within LMICs with rates ranging between 34.4% in Ho Chi Min City, Vietnam [49] to 74.6% in an urban area in Tamil Nadu, India [50] and 81% among urban households in Quito, the 2nd largest city in Ecuador [51].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Findings from the present study show that almost 50% of interviewed households reported food insecurity with 42% suffering from moderate to severe food insecurity and 8% living with mild food insecurity. The prevalence of moderate to severe food insecurity among Beirut residents was found to be higher than that reported earlier by rural households in the Bekaa region and another semi-urban Southern Lebanese population (34% and 42%, respectively) [11, 12]. However, comparable food insecurity levels to those reported in Greater Beirut area were observed among urban communities within LMICs with rates ranging between 34.4% in Ho Chi Min City, Vietnam [49] to 74.6% in an urban area in Tamil Nadu, India [50] and 81% among urban households in Quito, the 2nd largest city in Ecuador [51].…”
Section: Discussionmentioning
confidence: 71%
“…The Arabic version of the HFIAS was also tested for criterion-related validity and showed strong and consistent associations with various household characteristics, including total number of children in the household, family monthly income, crowding index, educational levels of mother and father, and number of cars. In addition, the same tool was found to be significantly associated with anthropometric measures [11]. This 9-question scale produces a total score between 0 and 27 with higher scores indicating greater food insecurity [33].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Lebanon, for example, the AFFSS determined that 42% of Lebanese citizens living in the south of the country were food and nutrition insecure, and 62% of Palestinian refugees living in Lebanon were food and nutrition insecure (Sayhoun et al 2014). Such elevated levels are relatively consistent with findings from the HFIAS, which showed that nearly 52% of Lebanese households in the Bekaa Valley are food and nutrition insecure (Naja et al 2014) (Table 1). …”
Section: The Example Of Lebanon: Varying Food and Nutrition Security mentioning
confidence: 74%
“…Both (a) and (b) were adapted by researchers at the American University of Beirut (AUB) from tools originally developed by the United States Agency for International Development (USAID). The AFFSS and HFIAS rely on survey responses, anthropomorphic measurements, and dietary intake information (Naja et al 2014;Sayhoun et al 2014). …”
Section: How Is Food and Nutrition Security Measured?mentioning
confidence: 99%